VD_FINDINFO Jug / 2012 / 65 vom 24. Februar 2012 - VD Tribunal cantonal (2012)
INSTITUTION SUPPLÉTIVE, LF SUR LA PRÉVOYANCE PROFESSIONNELLE VIEILLESSE, SURVIVANTS ET INVALIDITÉ, AFFILIATION AUX CAISSES, EMPLOYEUR | 11 LPP, 12 LPP, 54 al. 4 LPP, 60 al. 2bis LPP, 60 LPP, 73 al. 1 LPP, 73 al. 2 LPP, 109 al. 1 LPA-VD, 55 al. 1 LPA-VD, 82 LPA-VD, 33 let. h LTAF, 35 let. a LTAF